Comparison Between the Kernel Functions Used in Estimating the Fuzzy Regression Discontinuous Model - Mohammad Jasim Mohammad; Sajad Sammer Abd Al-Razzaq (Journal of Techniques)
Some experiments need to know the extent of their usefulness to continue providing them or not. This is done through the fuzzy regression discontinuous model, where the Epanechnikov Kernel and Triangular Kernel were used to estimate the model by generating data from the Monte Carlo experiment and comparing the results obtained. It was found that the. Epanechnikov Kernel has a least mean squared error.